Maximal oxygen uptake and concentric isokinetic muscle strength in pubertal football trained and untrained boys of the same biological age - Athanasios Mandroukas; Jan Heller (Karolinum Press, 2019)
The purpose of the present study was to examine the effects of long term (prolonged) football training on maximal oxygen uptake (V̇O2) and isokinetic muscle strength in young football players and untrained boys of the same biological age. Twenty football competitive boys (mean age 14 ± 0 yrs; height 165.5 ± 8.5 cm; weight 59.9 ± 9.5 kg; years of training 7 ± 3) and eighteen untrained school boys (mean age 14 ± 0; height 168.22 ± 10.46 cm; weight 59.3 ± 9.9 kg) of the same biological age volunteered to participate in the study. Sexual maturation classified according to Tanner's stage 3. The football players participated both in their school's physical education program and in their football team training program while the untrained group participated only in their school's physical education program (2-3 times per week for 40 min). All subjects were tested for maximal oxygen uptake (V̇O2) and respiratory exchange ratio (RER) on the treadmill using an open circuit spirometry. The isokinetic peak torque values of quadriceps (Q) and hamstrings (H) as well as the H : Q strength ratios were recorded. Hcon : Qcon was calculated as the ratio of the peak concentric torque of H to the peak concentric torque of the Q. Results showed that the trained group had significantly lower heart rate in rest (p < 0.001), higher RER (p < 0.001), maximal blood lactate (BLmax) (p < 0.001) and higher V̇O2 max in both relative and absolute values (p < 0.001) compared to the untrained group. At angular velocities of 60 ° s−1 and 180 ° s−1 the relative peak torque of Q and H were significantly higher (Q = p < 0.01; H = p < 0.01). However, the absolute values of Q and H as well as the H : Q ratios at all angular velocities did not differ significantly between the two groups. The results suggest that systematic football training (intensity and duration) has a positive effect in metabolic capacity, cardiorespiratory system and neuromuscular function.